Masseteric nerve supercharge bypass in primary reconstruction of facial nerve - Vachata, Petr; Brusakova, Stepanka; Lodin, Jan; Sames, Martin (Acta neurochirurgica, 2019)
Facial paralysis is a severe disease and presents a formidable treatment challenge. A wide variety of surgical procedures are available with limited evidence. Major risk factors of suboptimal recovery include the duration of paralysis as well as higher age. In this paper, we demonstrate reconstruction of the facial nerve via an intratemporal end-to-end anastomosis and concomitant transfer of an intact masseteric nerve to the side of facial nerve trunk. The supercharge (reverse end-to-side) transfer resulted in preservation of target muscles and faster recovery. Masseteric supercharge bypass may be an acceptable surgical technique to restore muscle function in potentially higher risk cases.
Keywords: Anastomosis, Surgical; Masseter Muscle; faciální paralýza; nervus mandibularis; Nerve Transfer; anastomóza chirurgická; musculus masseter; Male; Mandibular Nerve; Aged; lidé; Facial Paralysis; mužské pohlaví; senioři; Facial Nerve; Humans; nervus facialis; nervový transfer